Implementasi pendidikan multikultural di sekolah menengah atas - Liana Astuty Siregar; Indah Rahmadani Putri; Yona Riska Amelia; Khaerani Harahap (Indonesian Counselor Association (IKI), 2024)
This study aims to evaluate the implementation of multicultural education at SMA Negeri 1 Angkola Timur, focusing on the methods used in teaching diversity values and the challenges faced in the existing social context. Multicultural education in Indonesia aims to increase respect for cultural, ethnic, religious and racial differences in a heterogeneous society. This research used a case study approach with qualitative methods, involving in-depth interviews, participatory observation and documentation analysis. The interview technique involved principals, teachers and students to explore their perceptions of the implementation of multicultural education, while observation focused on teaching and learning and extracurricular activities related to diversity. The results showed that multicultural education at SMA Negeri 1 Angkola Timur has been implemented through teaching diversity values in the Civic Education (PPKn) subject and extracurricular activities that support cultural diversity. However, significant challenges are found in students' understanding of the importance of diversity, especially in responding to social issues that develop in the community. Factors that support the implementation of multicultural education in this school include the commitment of school management, parents' participation and support from the government. This research makes a new contribution by deeply exploring the implementation of multicultural education at the senior high school level in an area that is less explored in the multicultural education literature, and offers recommendations to improve students' understanding of diversity in their daily lives.